RETRACTED : Pengembangan tes penjelasan ilmiah materi sistem ekskresi manusia untuk siswa SMP/MTs kelas VIII - Isna Istikhanif Farida; Muntholib Muntholib; A. M. Setiawan (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) to article entitle "Pengembangan tes penjelasan ilmiah materi sistem ekskresi manusia untuk siswa SMP/MTs kelas VIII" Vol. 1 No. 5 (2021)   This paper has been found to be in violation of the Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in AIP Conference Proceedings 2215, 020013 (2020)   The document and its content has been removed from Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) and reasnable effort should be made to remove all references to this article.